Giants Are Coming? Predicting the Potential Spread and Impacts of the Giant Asian Hornet (Vespa Mandarinia, Hymenoptera:Vespidae) in the Usa - Vergara-Egert, P; Alaniz-Baeza, A; Carvajal-Leon, M (John Wiley and Sons Ltd, 2021)
BACKGOUND: Biological invasions are a global concern in agriculture, food production and biodiversity. Among the invasive species, some hornets are known to have serious effects on honey bees, as found during the invasion of Vespa velutina in Europe. The recent findings of Vespa mandarinia individuals in Washington state in the west coast of the USA have raised alarm in the whole country. Here we estimate the potential spread of V. mandarinia in the USA, analyzing its potential impacts on honey bee colonies, economic losses in the honey bee industry and bee-pollinated croplands. RESULTS: We found that V. mandarinia could colonize Washington and Oregon states in the west coast and a significant proportion of the east coast. If this species spread across the country, it could threaten 95 216 ± 5551 honey bee colonies, threatening an estimated income of US$11.9 and 101.8 million for hive derived products and bee-pollinated crops production, respectively, while colonizing 60 837.8 km2 of bee-pollinated croplands. CONCLUSION: Our results suggest that V. mandarinia will have serious effects in the USA, raising the need for prompt monitoring actions and planning at different administrative levels to avoid its potential spread. © 2020 Society of Chemical Industry